Incidence of triple negative breast cancer at Rajendra Institute of Medical Sciences, Ranchi - Kumari, Priyanka; Bhaskar, Sumit; Ranjan, Rajiv; Sinha, Dipendra Kumar (International Surgery Journal, 2019)
Background: Breast carcinoma is the second most common carcinoma in women and accounts for 22% of all female cancer, which is more than twice the prevalence of cancer in women at any other site. Triple negative breast cancer, i.e., negative expression of oestrogen and progesterone receptors and HER2/neu receptors and accounts for approximately 10-17% of all breast carcinomas, is biologically aggressive, resistant to conventional cytotoxic chemotherapy treatment, and is associated with reduced survival compared to other subtypes of breast cancer. Methods: History, local examination, Various investigations like: FNAC of breast lump and axillary lymph node, USG of breasts and axilla, USG of whole abdomen and pelvis, Chest X-ray PA View etc, ER/PR and HER-2/neu status on the specimen sent for HPE were done. The prognostic implications on ER, PR and HER-2/neu receptors were assessed indirectly with the help of Nottingham prognostic index (NPI)). Results: A statistically significant correlation of ER/PR receptor status was found with tumour size, no. of lymph nodes, tumour grade and NPI, whereas HER2/neu receptor status had a statistically significant correlation with tumour size and no. of lymph node involved. Incidence of triple negative breast cancer in this Institute is 20%. Conclusions: ER, PR and HER2/neu receptor status is highly important predictor in cases of carcinoma breast which necessitates routine evaluation of these receptor statuses for better management of disease.